Amyloid‐Beta Positron Emission Tomography Imaging of Alzheimer's Pathology in Parkinson's Disease Dementia. Issue 4 (5th January 2016) - Akhtar, Rizwan S.; Xie, Sharon X.; Brennan, Laura; Pontecorvo, Michael J.; Hurtig, Howard I.; Trojanowski, John Q.; Weintraub, Daniel; Siderowf, Andrew D.
Abstract: Background: Neuronal loss and alpha‐synuclein (α‐syn) pathology are diagnostic of PD in the appropriate clinical context. However, some Parkinson's disease (PD) patients have comorbid Alzheimer's disease (AD) pathology on autopsy, including amyloid‐beta (Aβ) plaques and neurofibrillary tangles. Florbetapir ( 18 F) is a PET ligand that detects Aβ pathology. We hypothesized that florbetapir ( 18 F) imaging could detect Aβ pathology in PD dementia (PDD) patients before death. The aim of this study was to determine the utility of florbetapir ( 18 F) PET imaging in detecting Aβ pathology in patients with autopsy‐confirmed PDD. Methods: Five participants with PDD had florbetapir ( 18 F) PET imaging before death as a part of a longitudinal research study of cognitive decline in PD. PET scans were evaluated by expert raters blinded to clinical and neuropathological information. At autopsy, all 5 participants underwent semiquantitative assessments of regional Aβ and tau immunohistochemistry. Results: All participants met neuropathological criteria for PD. Two had both positive florbetapir ( 18 F) scans and Aβ‐positive plaques in multiple brain regions. Regional florbetapir ( 18 F) binding correlated with regional semiquantitative Aβ pathology in these cases. Three cases had negative florbetapir ( 18 F) scans. Two of these had significant tau pathology without Aβ pathology, consistent with PSP in 1 case and argyrophilic grain disease in the other. The last case had a low level of AD neuropathological change. Conclusions: Florbetapir ( 18 F) Aβ imaging can detect the presence of Aβ neuropathology in patients with PDD. This imaging technique may aid the clinical evaluation of PDD patients to determine whether cognitive decline is occurring in the setting of Aβ accumulation.